Evaluation of Stromal CD10 Expression In Gastric Adenocarcinoma - Mukta, Rowshan Akter; Sultana, Zakiya; Rahman, Jenifer; Alahi, Mohammed Fazla; Bhattacharjee, Pradip (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Gastric cancer is the fifth most common cancer in the world. The stroma assumes a noteworthy part in the growth and progression of gastric carcinoma regardless of its epithelial nature. Accumulating data indicate that CD10 expression by stromal cells is involved in carcinogenesis. This study aimed to assess the immunohistochemical expression of CD10 in stromal cells of gastric adenocarcinoma and its association with some clinicopathological parameters. Materials and methods: This cross-sectional study was carried out at the Department of Pathology, Chittagong Medical College, from March 2021 to December 2022. A total of 50 cases of gastric adenocarcinoma, represented by formalin-fixed paraffin-embedded tissue blocks, were included in the study. Hematoxylin and Eosin (H&E)stained slides from each case were examined to assess the tumour grade, depth of invasion and nodal metastasis. Additionally, an immunohistochemical analysis was conducted to evaluate CD10 expression in the stromal cells of the tumour samples. Results: CD10 expression in stromal cells was detected in 64% of the cases. Furthermore, stromal CD10 expression showed a significant association with the depth of tumor invasion (p = 0.014). However, stromal CD10 expression had no significant association with age (p=0.434) sex (p=0.147) tumor type (p=0.375) histological grade (p=0.518) and nodal metastasis (p=0.092). Conclusion: Present study and previous studies support that stromal CD10 expression may be regarded as a negative prognostic indicator for gastric adenocarcinoma. JCMCTA 2025 ; 36 (1) : 134-140